2005
DOI: 10.1136/pgmj.2004.031229
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation in acute cardiogenic pulmonary oedema

Abstract: Non-invasive ventilation (NIV) is the delivery of assisted mechanical ventilation to the lungs, without the use of an invasive endotracheal airway. NIV has revolutionised the management of patients with various forms of respiratory failure. It has decreased the need for invasive mechanical ventilation and its attendant complications. Cardiogenic pulmonary oedema (CPO) is a common medical emergency, and NIV has been shown to improve both physiological and clinical outcomes. From the data presented herein, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 62 publications
1
40
0
9
Order By: Relevance
“…Secondly, the mean arterial pressure and heart rate after intubation were similar to baseline levels. Again, this is remarkable, as in most previous pressor response studies, both arterial pressure and heart rate following intubation were found to be significantly greater than not only the pre-intubation levels but also the preinduction levels [1,3]. One can only assume that their anaesthetic technique, which included fentanyl 100 lg and isoflurane 2%, considerably attenuated the cardiovascular responses and, indeed, may have contributed to their failure to find differences in the responses to intubation between the two groups.…”
Section: A Replymentioning
confidence: 68%
See 2 more Smart Citations
“…Secondly, the mean arterial pressure and heart rate after intubation were similar to baseline levels. Again, this is remarkable, as in most previous pressor response studies, both arterial pressure and heart rate following intubation were found to be significantly greater than not only the pre-intubation levels but also the preinduction levels [1,3]. One can only assume that their anaesthetic technique, which included fentanyl 100 lg and isoflurane 2%, considerably attenuated the cardiovascular responses and, indeed, may have contributed to their failure to find differences in the responses to intubation between the two groups.…”
Section: A Replymentioning
confidence: 68%
“…Firstly, the mean arterial pressure following Macintosh laryngoscopy actually fell from the baseline level taken immediately before laryngoscopy. This is difficult to understand as it has long been known that Macintosh laryngoscopy alone causes a significant rise in arterial pressure and catecholamine levels [3]. Secondly, the mean arterial pressure and heart rate after intubation were similar to baseline levels.…”
Section: A Replymentioning
confidence: 91%
See 1 more Smart Citation
“…Se han publicado nueve revisiones sistemáticas y/o meta-análisis [41][42][43][44][45][46][47][48][49] . La primera revisión sistemáti-ca, publicada en 1998 por Pang y cols 46 , no logró demostrar una reducción significativa de la tasa de intubación ni de la mortalidad al emplear CPAP, pero sólo incluyó tres estudios (n = 179).…”
Section: Resumen De La Evidenciaunclassified
“…................................................................................................................................................................................................................. Non-invasive ventilation (NIV) has revolutionised the management of diverse forms of respiratory failure [1]. It decreases the need for tracheal intubation and, in specific instances, also decreases mortality [2,3]. However, the role of NIV in acute neuromuscular respiratory failure is controversial.…”
Section: ó 2006 the Association Of Anaesthetists Of Great Britaimentioning
confidence: 99%